Analysis of clinical factors and reasons that influence the disposition of cryopreserved embryos in Japanese patients with infertility treated in our clinic. Issue 4 (15th February 2021) - Nakagawa, Yuko; Onogi, Sachie; Zhang, Shi‐Qing; Nishihara, Seiko; Ito, Masanori; Ando, Satoko; Tanaka, Kei; Tsuchiyama, Satoshi; Yamasaki, Hiroyuki; Shinohara, Kazunori; Okuno, Takashi; Kobayashi, Tamotsu; et al.
Abstract: Aim: To investigate the clinical factors and factors that affect the decisions regarding storage of cryopreserved embryos obtained using assisted reproductive technology. Methods: Clinical characteristics affecting the decisions regarding cryopreserved embryos were analyzed in 5724 Japanese couples who underwent in vitro fertilization (IVF) or intra‐cytoplasmic sperm insemination (ICSI) and embryo transfer over 4 years since April 2015 at our clinic. Statistical analysis was carried out using JMP software. Results: The number of oocytes retrievals and embryos stored, outcomes and number of children, and age of the female patients and male partners were related to the decision‐making regarding cryopreserved embryos. Childbearing and no wish for another child were the major reasons for discontinuing embryo storage. The number of oocytes retrievals and embryos in storage, age of the female patients, and sex of the child were independently associated with this decision‐making in 2682 patients with a single child. Women with male children were more likely to choose discontinuation of embryo storage than those with female children. Conclusion: Already having a child and not wishing for further treatment due to age along with the presence of a male child affect the decision to continue or discontinue embryo storage in Japanese patients with infertility.